An electric field cell for performing in situ single‐crystal synchrotron X‐ray diffraction. Issue 5 (4th September 2021) - Saunders, Lucy K.; Yeung, Hamish H.-M.; Warren, Mark R.; Smith, Peter; Gurney, Stuart; Dodsworth, Stephen F.; Vitorica-Yrezabal, Inigo J.; Wilcox, Adrian; Hathaway, Paul V.; Preece, Geoff; Roberts, Paul; Barnett, Sarah A.; et al.
Abstract : This paper describes the design and implementation of an electric field sample cell, used to perform in situ single‐crystal synchrotron X‐ray diffraction under an applied electric field and suitable for single‐crystal samples that are greater than 100 µm in size. Abstract : With the recent increase in research into ferroelectric, anti‐ferroelectric and piezoelectric materials, studying the solid‐state properties in situ under applied electric fields is vital in understanding the underlying processes. Where this behaviour is the result of atomic displacements, crystallographic insight has an important role. This work presents a sample environment designed to apply an electric field to single‐crystal samples in situ on the small‐molecule single‐crystal diffraction beamline I19, Diamond Light Source (UK). The configuration and operation of the cell is described as well as its application to studies of a proton‐transfer colour‐change material.